Phenolic acids and antioxidative capacity on ancient wheat namely einkorn (T. monococcum ssp.), emmer (T. turgidum ssp.) and spelt wheat (T. aestivum ssp. spelta) and on germinated bread wheat (T. aestivum ssp. aestivum) - Engert, Nadine; Justus Liebig University Giessen (My University, 2011)
The focus of the thesis was on content and composition of phenolic acids in grains ofdifferent wheat species as natural antioxidants. The analysis was carried out with HPLCmethod and with Folin-Ciocalteu and ORAC (oxygen radical absorbance capacity) assay.Experiment 1 was an evaluation of ancient wheat species including einkorn, emmer and speltwheat. Ferulic acid (FA) as one analyzed phenolic acid was the abundant one with about65 % of all analyzed phenolic acids. For the analyses three fractions (soluble free, solubleconjugated and bound phenolic acids) were extracted and most phenolic acids were foundas bound forms.Experiment 2 was a sprouting experiment with bread wheat cultivars. The experiment wasconducted to see whether sprouting influenced the phenolic acid contents and theantioxidative capacity. Ferulic acid was the predominant phenolic acid in all three sproutingsteps (not sprouted, presprouted and fully sprouted) with 67 % for not sprouted and 54 % forfully sprouted samples. Bound phenolic acids contributed the main part of the total phenolicacids although sprouting had an influence on that.The third experiment evaluated spelt wheat cultivars as the most important ancient wheatspecies. Similar results to the first experiment were found with ferulic acid as the abundantphenolic acid. Fraction 3 (bound phenolic acids) was the predominant fraction for thatexperiment as well. In general, TPA contents and composition along with FA contents werecomparable to the literature. No evolutionary changes seem to be present in the compositionof phenolic acids with FA as the abundant phenolic acid in ancient wheat plus in modernwheat species.The antioxidative capacity by Folin-Ciocalteu was expressed as total phenolic contents(TPC). The bound fraction contributed the highest TPC values in all experiments. Theantioxidative capacity by the ORAC assay showed lower values of experiment 1 and 3 thanof experiment 2. Sprouting time of 48 hours led to significant increase the antioxidativecapacity of wheat grains in comparison with shorter sprouting time.Thus, ancient wheat, sprouted wheat and bread wheat do not only consist of basic nutrientssuch as carbohydrates, protein, dietary fiber, vitamins or minerals they also containsecondary plant metabolites like phenolic acids. Their ability to scavenge free radicals andtherefore their antioxidative potential makes them interesting in order to reduce the risk ofchronic diseases.

Gegenstand der Dissertationsschrift war die Analyse des Vorkommens und derZusammensetzung von Phenolsäuren in Weizenkaryopsen und die Bewertung derantioxidativen Kapazität. Die Detektion der Phenolsäuren erfolgte mit einer HPLC-Methode,während die antioxidative Kapazität durch Folin-Ciocalteu und ORAC (oxygen radicalabsorbance capacity) Assay bestimmt wurden. Die Untersuchungen führten zu folgendenErgebnissen:Im Experiment 1 wurden alte Weizenarten wie Einkorn, Emmer und Dinkel untersucht. Eswurde festgestellt, dass in allen Weizenarten die Ferulasäure (FA) mit 65 % der gesamtenPhenolsäuren den Hauptanteil einnahm. Die meisten Phenolsäuren kommen dabei ingebundener Form vor. Im Experiment 2 (Keimungsversuche mit Brotweizensorten) wurdeder Einfluss der Keimung auf die Phenolsäuregehalte und auf die antioxidative Kapazitätuntersucht. Es wurde beobachtet, dass die Ferulasäure in allen drei Keimungsstufen, nichtgekeimt (0 h), angekeimt (24 h) und durchgekeimt (48 h), mit 67 % bei den nicht gekeimtenund mit 54 % bei den vollständig gekeimten Weizenproben die Hauptphenolsäure war. Dengrößten Anteil der gesamten Phenolsäuren liefern die gebunden Phenolsäuren. Im drittenExperiment wurden verschiedene Sorten von Dinkelweizen aus unterschiedlichenStandorten untersucht. Es wurde beobachtet, dass auch in diesem Experiment dieFerulasäure als Hauptphenolsäure auftrat. Die meisten Phenolsäuren sind als gebundeneBestandteile aus Fraktion 3 zu finden. Die in den eigenen Experimenten gefundenenKonzentrationen an Gesamtphenolsäuren und an Ferulasäure stimmen mit den Werten derLiteratur überein.Die antioxidative Kapazität nach Folin-Ciocalteu wird als Gesamtphenolgehalt (TPC)ausgedrückt. Die höchsten TPC-Werte wurden in allen drei Experimenten mit dengebundenen Phenolsäuren ermittelt. Die antioxidative Kapazität des ORAC-Assays zeigte inden Experimenten 1 und 3 niedrigere Werte als in Experiment 2. Die Keimungsdauer von 48Stunden führte im Vergleich zu einer kürzeren Keimungsdauer zu einem signifikantenAnstieg der antioxidativen Kapazität.Insgesamt wird fest gestellt, dass die Expression von Phenolsäuren in verschiedenenWeizenarten relativ stabil ist. Der Gehalt und die Zusammensetzung der Phenolsäurenhaben sich im Laufe der Evolution des Weizens offenbar nicht wesentlich verändert.Weizenkaryopsen und deren Vermahlungsprodukte besitzen mit den Phenolsäurenantioxidativ wirksame Verbindungen, die zu einer gesunden Ernährung des Menschenbeitragen können.
Phenolsäuren und antioxidative Kapazität alter Weizen namentlich Einkorn (T. monococcum ssp.), Emmer (T. turgidum ssp.) und Dinkelweizen (T. aestivum ssp. spelta) and gekeimter Weizen (T. aestivum ssp. aestivum)
Keywords: alte Weizen; Phenolsäuren; antioxidative Kapazität; Einkorn; Emmer; Dinkel; ancient wheat; phenolic acids; antioxidative capacity; einkorn; emmer; spelt; ddc:630